Hydrological impacts of moderate and high-end climate change across European river basins - Lobanova, A.; Liersch, S.; Nunes, J.; Didovets, I.; Stagl, J.; Huang, S.; Koch, H.; Rivas López, M.; Fox Maule, C.; Hattermann, F.; Krysanova, V. (Journal of Hydrology: Regional Studies, 2018)
Study region: To provide a picture of hydrological impact of climate change across different climatic zones in Europe, this study considers eight river basins: Tagus in Iberian Peninsula; Emån and Lule in Scandinavia; Rhine, Danube and Teteriv in Central and Eastern Europe; Tay on the island of Great Britain and Northern Dvina in North-Eastern Europe. Study focus: In this study the assessment of the impacts of moderate and high-end climate change scenarios on the hydrological patterns in European basins was conducted. To assess the projected changes, the process-based eco-hydrological model SWIM (Soil and Water Integrated Model) was set up, calibrated and validated for the basins. The SWIM was driven by the bias-corrected climate projections obtained from the coupled simulations of the Global Circulation Models and Regional Climate Models. New hydrological insights for the region: The results show robust decreasing trends in water availability in the most southern river basin (Tagus), an overall increase in discharge in the most northern river basin (Lule), increase in the winter discharge and shift in seasonality in Northern and Central European catchments. The impacts of the high-end climate change scenario RCP 8.5 continue to develop until the end of the century, while those of the moderate climate change scenario RCP 4.5 level-off after the mid-century. The results of this study also confirm trends, found previously with mostly global scale models.